Transformasi Sosial Budaya Masyarakat pada Implementasi Program Smart Village dalam perspektif Smart Governance. - Agus Widiyarta; Ananda Haniyuhan; Katerina Bataha (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Smart Village is defined as a service that utilizes information technology in carrying out various activities in the village and is managed by the community effectively and efficiently. Limpung Village is one of the pilot villages for the implementation of the smart village program in Batang Regency. The existence of the implementation of the smart village program has created changes in the order of public services that concern the interests of the wider community in Limpung Village. This study aims to examine the influence of the implementation of the smart village program in relation to socio-cultural transformation in a smart governance perspective. The data in this study will be obtained by means of interviews and observations and presented with a qualitative descriptive method. The results of this study can be seen that in the perspective of smart governance which is one of the components of the smart village concept in relation to the implementation of the smart village program, it has created a social transformation of society seen from the cultural background and the direction of socio-cultural transformation. In the focus of the cultural background, a significant influence occurs in a pattern of community transformation that previously carried out public services manually, now starting to switch to using digital methods. In terms of direction and socio-cultural transformation, it shows that the implementation of the smart governance component is aimed at creating an advanced society in accordance with the era of society 5.0.